2014
DOI: 10.7314/apjcp.2014.15.22.9713
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Serum Vascular Endothelial Growth Factor and Complement 3a Levels in Patients with Colorectal Cancer in Southern Iran

Abstract: Background: Colon cancer (CRC) is perhaps the second most common cause of cancer mortality. This study determined the clinical significance of serum vascular endothelial growth factor (VEGF) and serum complement 3a (C3a) levels in patients with CRC in Fars province, southern Iran. Materials and Methods: Between June 2010 and June 2012, 110 patients with CRC of both genders and different age groups were divided into 3 groups. Group A included patients who had just undergone surgery; Group B had undergone chemot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…The highest mortality rates occur in Central and Eastern European countries, and the lowest (15). In China in 2009, colorectal cancer incidence and mortality rates were higher than the world averages: Rates were than lower that observed in Japan, Singapore and South Korea, but higher than that of countries such as Iran, Laos and India (16,17). In the present study, it was demonstrated that naphthazarin significantly decreased cell viability, increased cytotoxicity and induced cellular and nuclear apoptosis of SW480 cells in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…The highest mortality rates occur in Central and Eastern European countries, and the lowest (15). In China in 2009, colorectal cancer incidence and mortality rates were higher than the world averages: Rates were than lower that observed in Japan, Singapore and South Korea, but higher than that of countries such as Iran, Laos and India (16,17). In the present study, it was demonstrated that naphthazarin significantly decreased cell viability, increased cytotoxicity and induced cellular and nuclear apoptosis of SW480 cells in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in VEGF expression in tumour tissue or blood compartments (i.e. serum or plasma) has been found in solid and hematological malignancies of various origins and is associated with metastasis formation and poor prognosis (15,16). By multivariate analysis of molecular markers for detection of liver metastases after surgery in patients with colorectal cancer, it was demonstrated that a combination of markers such as carcinoembryonic antigen (CEA), epidermal growth factor receptor (EGFR) and VEGF could be an effective method for predicting liver metastases in patients with colorectal cancer (17).…”
mentioning
confidence: 99%
“…Prior studies had reported that inflammatory proteins were associated with tumor prognosis and progression, and displayed the predictive significance in different human cancers. For example, patients with elevated preoperative CRP had a poor survival in UTUC, 58 60 and high complement 3 levels were shown to be related to poor prognosis in patients with colorectal cancer, 61 and an increased preoperative gamma globulin levels predicted poor survival in lung cancer. 62 In addition, the globulins were shown to be closely related with chronic inflammation.…”
Section: Discussionmentioning
confidence: 99%